Land and Water Management In Pineapple and Sengon Agroforestry Systems in Peatland - Momon Sodik Imanudin (Sriwijaya Journal of Environment, 2019)
Fires of land and forests on peatland occur every year. This problem is triggered by the burning of land that is not cultivated, or the business of land clearing by community group that does an open fire which is less costly. Because of this condition, people need to find alternative efforts to use peat without burning the land. The agroforestry model is an effort carried out by utilizing land for wood industry plants and the seasonal crops (agriculture) are planted among the main crops. This effort encourages partnerships between private parties and local residents. Field applications have been carried out in the Sumatra Alam Anugrah LLC concession area, in Gumai Village, Teluk Rumai Village, Gelumbang sub-district. Sengon plants are used as main plants, while pineapple plants are intercrop plants, which are expected to contribute to the income of local residents. Results of the study showed that soil characteristics were characterized by porosity ranging from 90 to 95% and soil content of 0.2 gr / cm3. The movement of water in the soil was very fast. In order to manage the land and water of the study area it is suggested to apply a concept of water control that is a shallow drainage, namely the primary channel that has a depth of 2 m, the secondary channel, and tertiary channel that were made with a depth of 1 m. In the plot of the land a worm channel is made with a distance between 50 channels and a depth of 40 cm. With this shallow water system, the depth of the groundwater can be maintained at an altitude of 30 to 40 cm, so that it is suitable for pineapple growth and also prevention of land fires.